Tubercular meningitis: a rare cause of convulsions in pregnancy. (18th April 2012) - Coleman, LC; Bahl, R; Liebling, R; Medd, E
Abstract : Introduction: Eclampsia is a common cause of new onset self-terminating tonic-clonic seizures in term pregnancy. Other causes of seizures such as epilepsy and central nervous system infection, haemorrhage, infarction, mass or thrombosis are considered as differential diagnoses when there is atypical presentation. Case report: A 25 year old Somalian woman presented to delivery suite at 38 weeks of pregnancy with a 12 hour history of headache, confusion and one episode of self-terminating tonic-clonic seizure. She was in her third uncomplicated pregnancy with the past medical history of tubercular sacroiliitis. She completed anti-tubercular treatment and was discharged from the TB clinic prior to this pregnancy. On arrival to the delivery suite the patient was confused, agitated and combative. Her blood pressure was normal. It was difficult to accurately assess her neurological state due to her degree of agitation. However bilateral upgoing plantars were noted with no other apparent neurological abnormality. A presumed diagnosis of eclampsia was made. Magnesium sulphate infusion was commenced with no improvement in clinical condition. The patient was intubated for further investigation and management. A lower segment caesarean section was performed and she was transferred to the intensive care unit for ventilatory support. Following extensive investigation she was diagnosed with TB meningitis and bilateral parietal tuberculomas. Conclusion: The purpose of this report is to illustrate a relatively rare cause of seizures in pregnancy. With TB affecting an increasing number of patients in UK hospitals, it is an important differential diagnosis for a vast range of presenting complaints.